Self-introduction of an electric wire into the urinary bladder - Noushim Akram Huda; Krishnendu Maiti (Annals of Medical Science and Research)
The bladder is the most common site of foreign bodies in the urinary tract. We are presenting a case of a 39-year-old male who self-introduced an electrical wire into bladder. The wire was removed by suprapubic cystotomy after failed endoscopic retrieval. The case is presented for its rarity, along with a review of the literature.